2011
DOI: 10.1016/j.bone.2011.01.019
|View full text |Cite
|
Sign up to set email alerts
|

FOXO1 modulates osteoblast differentiation

Abstract: Forkhead box O1 (FOXO1) is upregulated during bone formation and in response to stimulation by bone morphogenetic proteins. Studies presented here examined the functional role of FOXO1 in a well defined culture system in which pre-osteoblastic cells undergo terminal differentiation in vitro. Mineralizing cultures of MC3T3-E1 cells were examined with or without FOXO1 knockdown by RNAi. Normal cells show the upregulation of FOXO1 and RUNX2 DNA binding activity, alkaline phosphatase activity, and mRNA levels of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 30 publications
2
81
0
Order By: Relevance
“…The FOXO protein family, one of several known downstream targets of activated AKT, has been associated with expression of Runx2 in osteoblasts, human embryonic stem cells and prostate cancer cells, although data from these studies are not compelling 3134 . We found that FOXO1 and FOXO3a are highly expressed in VSMC compared with FOXO4 (Online Supplemental Fig II).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FOXO protein family, one of several known downstream targets of activated AKT, has been associated with expression of Runx2 in osteoblasts, human embryonic stem cells and prostate cancer cells, although data from these studies are not compelling 3134 . We found that FOXO1 and FOXO3a are highly expressed in VSMC compared with FOXO4 (Online Supplemental Fig II).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested a potential link between FOXO and Runx2 expression in other cell types 3134 . In osteoblasts and human embryonic stem cells, FOXO1 or FOXO3 increases Runx2 expression; whereas other studies suggest that FOXO1 inhibits Runx2 activity in osteoblasts or prostate cancer cells 3134 . Therefore, the function of FOXOs in regulating Runx2 expression may be cell type-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…P Ͻ .01 compared with control siRNA. doi: 10.1210/me.2013-1152 mend.endojournals.org cells (43,44). It has been shown that Foxo1 can interact directly with Runx2, although the exact impact of Foxo1 on Runx2 functional activity is controversial (27)(28)(29).…”
Section: Discussionmentioning
confidence: 97%
“…As shown in Supplementary Fig. S1, different genes involved in osteogenic differentiation are upregulated in ATP-treated BM-hMSCs compared to the untreated sample, such as osteoblastic transcription factors (ie, RUNX2 [38] and FOXO1 [39]), osteoblastic markers (ie, ANKH, BGLAP, and SPP1 [40,41]), and osteogenic growth factors (ie, BMP2, BMP6, WISP2, and IGFBP5 [42][43][44][45]). Moreover, ATP treatment of BM-hMSCs increased the expression of adipogenic transcription factors (ie, CEBPA, PPARGC1A, and CEBPB) [46] and adipocytespecific proteins (ie, ADFP, PC, and SPG20 [47][48][49]) (Supplementary Fig.…”
Section: Gene Expression Profile Of Atp-treated Undifferentiated Bm-hmentioning
confidence: 99%